Persulphide-responsive transcriptional regulation and metabolism in bacteria. (6th August 2019) - Shimizu, Takayuki; Masuda, Shinji
Abstract: Hydrogen sulphide (H2 S) impacts on bacterial growth both positively and negatively; it is utilized as an electron donor for photosynthesis and respiration, and it inactivates terminal oxidases and iron-sulphur clusters. Therefore, bacteria have evolved H2 S-responsive detoxification mechanisms for survival. Sulphur assimilation in bacteria has been well studied, and sulphide:quinone oxidoreductase, persulphide dioxygenase, rhodanese and sulphite oxidase were reported as major sulphide-oxidizing enzymes of sulphide assimilation and detoxification pathways. However, how bacteria sense sulphide availability to control H2 S and sulphide metabolism remains largely unknown. Recent studies have identified several bacterial (per)sulphide-sensitive transcription factors that change DNA-binding affinity through persulphidation of specific cysteine residues in response to highly reactive sulphur-containing chemicals and reactive sulphur species (RSS). This review focuses on current understanding of the persulphide-responsive transcription factors and RSS metabolism regulated by RSS sensory proteins.